RETAINING STYLE WITHOUT HARMING FIDELITY: A CASE OF TRANSLATING PAULINE METAPHORS - Prajoko, Dwi Aji (Universitas Sebelas Maret, 2012)
The objectives of this study are to legitimize the retention of metaphors in the translation when they do not harm meaning and dynamic fidelity, to assess renderings on the basis of their fidelity, and to suggest alternative renderings for the ones violating the fidelity. This study shows surprising findings. Applying Lakoff and Johnson’s (1980) metaphorical concepts on Pauline metaphors, the researcher finds that many English and Indonesian metaphors have the same metaphorical concepts. This potentially makes the retention of the metaphors in the rendering meaningful or natural due to its match with the dynamic fidelity. The context of the meaningful metaphors, then, must be analyzed to determine the accuracy or meaning fidelity. This study echoes the notion that style is as important as meaning (Mahmkjer, 2004; Shi, 2006:10), even though Nida and Taber (1969) strongly suggest that meaning must be the top priority when it is in tension with style in their translation. To the translators, this study suggests not hastily discarding metaphors in the translation, replacing them with non-metaphors and, therefore, missing the significance of metaphors.Key words: metaphor, translation, fidelity